Technique of Coaxial Frame in Reflection for the Characterization of Single and Multilayer Materials with Correction of Air Gap - Zarral Lamia; Djahli Farid; Ndagijimana Fabien (International Journal of Antennas and Propagation)
Techniques based on fixture probes in reflection are used in microwave reflectometry as a novel diagnostic tool for detection of skin cancers, for complex permittivity measurements on liquid samples and oil shale, and for complex dielectric permittivity of animals’ organs and tissues measurements in microwave band for the needs of modern veterinary medicine. In this work, we have developed a technique to characterize multilayer materials in a broadband frequency range. A coaxial probe in reflection has been specially developed for microelectronic substrate. Using SMA connector, loss tangent of 10−4 and relative permittivity have been measured with an error of 0.145%. The extension of the coaxial probe in reflection technique to multilayer substrates such as Delrin and Teflon permitted to measure bilayer material provided the good knowledge of electrical parameters and dimensions of one layer. In the coaxial transmission line method, a factor that greatly influences the accuracy of the results is the air gaps between the material under test and the coaxial test fixture. In this paper, we have discussed the influence of the air gaps (using samples of 0.5 mm air gaps) and the measures that can be taken to minimize that influence when material is measured. The intrinsic values thus determined have been experimentally verified. We have described the structure of the test fixture, its calibration issues, and the experimental results. Finally, electromagnetism simulations showed that the best results can be obtained.